A Visitors Center at the Washington Monument: an entry in the ASC/AIA Tile Council of America - Jeff Cutberth; Ed DeVilbiss; J. C. Heintzelman (Oz, 1981)
This proposal responded to the dual purpose established in the program for a visitors center for the nation's capitol and a waiting area for visitors to the Washington Monument…